Divergent Ah Receptor Ligand Selectivity during Hominin Evolution. (2nd August 2016) - Hubbard, Troy D.; Murray, Iain A.; Bisson, William H.; Sullivan, Alexis P.; Sebastian, Aswathy; Perry, George H.; Jablonski, Nina G.; Perdew, Gary H.
Abstract: We have identified a fixed nonsynonymous sequence difference between humans (Val381; derived variant) and Neandertals (Ala381; ancestral variant) in the ligand-binding domain of the aryl hydrocarbon receptor ( AHR ) gene. In an exome sequence analysis of four Neandertal and Denisovan individuals compared with nine modern humans, there are only 90 total nucleotide sites genome-wide for which archaic hominins are fixed for the ancestral nonsynonymous variant and the modern humans are fixed for the derived variant. Of those sites, only 27, including Val381 in the AHR, also have no reported variability in the human dbSNP database, further suggesting that this highly conserved functional variant is a rare event. Functional analysis of the amino acid variant Ala381 within the AHR carried by Neandertals and nonhuman primates indicate enhanced polycyclic aromatic hydrocarbon (PAH) binding, DNA binding capacity, and AHR mediated transcriptional activity compared with the human AHR. Also relative to human AHR, the Neandertal AHR exhibited 150–1000 times greater sensitivity to induction of Cyp1a1 and Cyp1b1 expression by PAHs (e.g., benzo( a )pyrene). The resulting CYP1A1/CYP1B1 enzymes are responsible for PAH first pass metabolism, which can result in the generation of toxic intermediates and perhaps AHR-associated toxicities. In contrast, the human AHR retains the ancestral sensitivity observed in primates to nontoxic endogenous AHR ligands (e.g., indole, indoxyl sulfate). Our findings reveal that a functionally significant change in the AHR occurred uniquely in humans, relative to other primates, that would attenuate the response to many environmental pollutants, including chemicals present in smoke from fire use during cooking.